Milet, Türkei: Die letzte byzantinische Siedlung auf dem Theaterhügel - Fildhuth, Jesko (e-Forschungsberichte des DAI, 2023)
In the 2013/14 campaign, a geophysical survey in combination with small scale excavations was conducted on the Kaletepe of Miletus, aiming at the study of the development of the medieval city. The Byzantine settlement of Miletus was newly established in this area during the 12th-13th century, representing the last phase of the byzantine city before the beginning of the Islamic period.